Report of the Working Group on Health Care for Women and Children for Tenth Five year Plan - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Working Group on Health Care for Women and Children for the Tenth Five Year Plan (2001–2007) presents a comprehensive framework for assessing disease burden, reviewing reproductive and child health programmes, and strengthening health systems in India. Recognizing women and children as socio-economically vulnerable groups, the report emphasizes the need for reliable and disaggregated data to guide policy formulation and priority setting. It outlines detailed classification schemes for causes of disease burden among women (above 15 years) and children (0–14 years), covering maternal conditions, reproductive disorders, infectious diseases, nutritional deficiencies, socio-economic determinants, and other major causes. The report highlights the importance of demographic inputs such as age-sex population distribution, age-specific death rates, cause-specific mortality proportions, and epidemiological indicators for estimating mortality and morbidity, including summary measures like Disability Adjusted Life Years (DALYs). It critically reviews data sources such as the Sample Registration System and Medical Certification of Cause of Death, identifying limitations in coverage, accuracy, and timeliness that affect planning and decentralized decision-making. Additionally, the Working Group evaluates ongoing reproductive health programmes, infrastructure, manpower, financial resources, and NGO/private sector participation, and proposes strategies to improve service delivery, enhance secondary and tertiary care, and ensure better utilization of facilities. Overall, the report underscores the need for strengthened data systems, targeted interventions, and integrated policy measures to reduce maternal and child mortality and improve reproductive health outcomes during the Tenth Plan period and beyond.
Government of India Planning Commission June - 2001
Keywords: Tenth Five Year Plan; Health Care for Women and Children; Disease Burden Estimation; Reproductive Health Programmes; Maternal Mortality Rate; Infant Mortality Rate; Classification of Causes of Death; Socio-Economic Vulnerability; Family Welfare Infrastructure; Cause of Death Reporting System; Sample Registration System; Disability Adjusted Life Years